BACTERIOPHAGE PATTERN AND METHICILLIN RESISTANCE OF STAPHYLOCOCCUS AUREUS ISOLATED FROM HOSPITALISED PATIENTS - MISRA, RN (Med J Armed Forces India, 1997)
Ninety two strains of Staphylococcus aureus isolated from hospitalized patients were phage grouped and phage typed and their resistance pattern to methicillin were studied. Forty five (48.9%) strains were nontypable, followed by mixed group in 23 (25%). The phage groups I, II, III, V and miscellaneous groups were 3.3 per cent, 7.6 per cent, 8.7 per cent, 1 per cent and 3.3 per cent respectively. Majority of the strains were methicillin resistant. Out of 45 nontypable strains 33 (73.3%) were methicillin resistant whereas in mixed phage group methicillin resistance was found in 52 per cent. The inadequacy of available phages for typing, rising incidence of methicillin resistance in untypable strains and variance of phage group and phage types at various places has been highlighted.